Azerbaijan country gender assessment. (Asian Development Bank, 2019)
Gender equality goals are cited in the national development policies and economic strategies of Azerbaijan. The country gender assessment included interviews with women in the communities who shared their stories and insights on how projects of the Asian Development Bank and other social interventions have improved their lives